Penerapan Terapi Bermain Mewarnai Pada Anak Prasekolah Yang Mengalami Kecemasan Hospitalisasi - Amalia, Luthfiana; Irdawati, Irdawati; Putri, Rosalia Dian Arsita (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Hospitalization of children is a procedure that requires children to be in health services to receive medical treatment until their condition recovers and they are allowed to go home. The reaction of preschool-aged children during the treatment period is anxiety. Anxiety occurs because the child feels a traumatic situation because he is separated from his daily environment. Coloring play therapy is an effective game option for children to play during their hospital stay. Applying coloring play therapy to reduce anxiety in children who are hospitalized. This case study uses a nursing care approach by applying coloring play therapy for 30 minutes given to three preschool age children who experienced anxiety due to hospitalization as measured using the Faces Anxiety Scale (FAS). Coloring play therapy was proven to reduce the anxiety scale in pre-school children due to hospitalization. Play therapy intervention can reduce anxiety in children undergoing hospitalization so that children become cooperative in receiving nursing actions Keywords : Coloring play therapy, Anxiety, Preschool Children ABSTRAK Hospitalisasi pada anak merupakan prosedur yang mengharuskan anak berada di pelayanan kesehatan untuk mendapat perawatan medis hingga kondisi pulih dan diperbolehkan pulang. Reaksi anak usia preschool selama masa perawatan adalah kecemasan, kecemasan terjadi karena anak merasakan situasi traumatis karena terpisah dari lingkungan sehari-hari. Terapi bermain mewarnai menjadi salah satu pilihan permainan yang efektif untuk dilakukan anak saat masa perawatan di rumah sakit. Menerapkan terapi bermain mewarnai untuk mengurangis kecemasan pada anak yang mengalami hospitalisasi. Studi kasus ini menggunakan  pendekatan asuhan keperawatan dengan menerapkan terapi bermain mewarnai selama 30 menit yang diberika pada tiga anak usia prasekolah yang mengalami kecemasan akibat hospitalisasi yang diukur menggunakan Faces Anxiety Scale (FAS). Terapi bermain mewarnai terbukti menurunkan skala kecemasan pada anak usia pra sekolah akibat hospitalisasi. Intervensi terapi bermain dapat menurunkan kecemasan pada anak  yang menjalani hospitalisasi sehingga anak menjadi kooperatif menerima tindakan keperawatan Kata kunci: Terapi Bermain mewarnai, Kecemasan, Anak Prasekolah